THE PRONOUN:ITS STRUCTURAL AND SEMANTIC CLASSIFICATIONS AND THE THEORY BEHIND ITS GRAMMATICAL CATEGORIE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive exploration of pronouns, focusing on their structural and semantic types as well as the theory of their grammaticalcategories. It categorizes pronouns into structural groups such as personal, possessive, reflexive, relative, demonstrative, indefinite, and interrogative, explaining the distinctfunctions each type performs in language. The article also delves into the semantic roles ofpronouns, including anaphoric, cataphoric, deictic, and exophoric uses, illustrating howpronouns link ideas across sentences and rely on context for meaning. Additionally, itcovers the grammatical categories of pronouns, including person, number, gender, case, formality, inclusivity, and reciprocity, highlighting their role in shaping sentence structureand communication. This article serves as an essential resource for understanding themultifaceted nature of pronouns and their central importance in language.